TINJAUAN KRIMINOLOGIS TERHADAP PRAKTIK PELACURAN DI KOTA MAKASSAR (Qawanin Jurnal Ilmu Hukum, 2021)
Prostitution is a phenomenon that has existed for a long time in the world, and Indonesia is no exception. Prostitution in Indonesia dates back to the days of the Javanese kingdoms that used women as part of the feudal system of commodities. The phenomenon of prostitution is still an unresolved problem.The practice of covert prostitution in Makassar City has become an open secret. There are several places in Makassar City that prepare women to satisfy lust, mostly under the guise of massage parlors, SPAs, pubs, cafes and karaoke places, to salons.In all these places there are beautiful and sexy women, they are ready to satisfy the masculine men and the most covert practices in Makassar City are massage parlors. Several locations such as in the Panakukang area, Nusantara road, Perintis Kemerdekaan road and Mount Latimojong road.